Evolution of the Symbiosis-Specific GRAS Regulatory Network in Bryophytes - Grosche, Christopher; Genau, Anne Christina; Rensing, Stefan A. (Frontiers in Plant Science, 2018)
Arbuscular mycorrhiza is one of the most common plant symbiotic interactions observed today. Due to their nearly ubiquitous occurrence and their beneficial impact on both partners it was suggested that this mutualistic interaction was crucial for plants to colonize the terrestrial habitat approximately 500 Ma ago. On the plant side the association is established via the common symbiotic pathway (CSP). This pathway allows the recognition of the fungal symbiotic partner, subsequent signaling to the nucleus, and initiation of the symbiotic program with respect to specific gene expression and cellular re-organization. The downstream part of the CSP is a regulatory network, that coordinates the transcription of genes necessary to establish the symbiosis, consists of multiple GRAS transcription factors. These regulate their own expression as an intricate transcriptional network. Deduced from non-host genome data the loss of genes encoding CSP components coincides with the loss of the interaction itself. Here, we analyzed bryophyte species with special emphasis on the moss Physcomitrella patens, supposed to be a non-host, for the composition of the GRAS regulatory network components. We show lineage specific losses and expansions of several of these factors in bryophytes, potentially coinciding with the proposed host/non-host status of the lineages. We evaluate losses and expansions and infer clade-specific evolution of GRAS transcription factors.